Muslim Women in Postcolonial Kenya : Leadership, Representation, and Social Change - Alidou, Ousseina (Book collections on Project MUSE., 2013)
In education, journalism, legislative politics, social justice, health, law, and other arenas, Muslim women across Kenya are emerging as leaders in local, national, and international contexts, advancing reforms through their activism. The author draws on extensive interviews with six such women, revealing how their religious and moral beliefs shape reform movements that bridge ethnic divides and foster alliances in service of creating a just, multicultural, multiethnic, and multireligious democratic citizenship. -- Description from publisher website.